Building Mass Optimization to Reduce Solar Radiation in High Rise Building by Using Parametric Approach - Qurrotul A'yun (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2024)
Buildings use 40% of global primary energy, therefore their design and use affect climate change. Building performance analysis can assist architects predict performance before construction with parametric design tools. Radiance can be reduced via a parametric mass, lowering cooling load and energy use. The study uses theoretical and computational research to explain, forecast, and analyze events, whereas parametric design optimizes complicated geometries using mathematical parameters and algorithms. Environmental analysis in Grasshopper with the Ladybug plugin uses Rhinoceros. This plugin provides solar radiation, and climate analysis capabilities. To determine the most energy-efficient building design, the research links independent and dependent variables such solar radiation intensity and building mass. The study uses Surabaya weather data and high rise buildings. The land is formed like a square, with a 15-degree slope to the north and is flanked by low-rise buildings. As a result, the location receives the most direct sunlight during the day. Then, solar radiation analysis. It helps optimize passive solar design solutions. According to the modelling results, solar radiation on the top and west sides are particularly large and dominant in 65.37 and 32.69 kWh/m2. Meanwhile, the north, east and south sides receive very little solar radiation. The following simulation considers the optimal direction, which is to extend west-east and face to the south. A multi-towered megastructure is a high-rise building that responds best to solar radiation. The total solar radiation value is 3,718,100 kWh. It can accommodate large spaces with large mass composition but relatively low total solar radiation values. The building towers provide shade to each other, thereby reducing direct radiation from the sun to the building. The sides of the building's podium are also shaded, so the top of the building is partially red.